A Framework for Clarifying the Goal and Implementation of ISO - Al-Hameed, Layla; Dobson, Philip; Jackson, Paul (ACIS, 2014)
Many organizations are dissatisfied with the outcomes of ISO implementations. This paper proposes that this dissatisfaction is often a consequence of a lack of clarity as to the goal of the implementation and the lack of a clear linkage to the organizational goal over the implementation. The paper proposes that the use of the relatively new tool from the Theory of Constraints – the Strategy and Tactic (S&T) tree can help to provide this linkage and to guide the subsequent implementation. The integration of the S&T Tree and Treacy and Wiersema’s Value Discipline model (1993) is used to focus the original goal setting and subsequent implementation. A case example is then presented to illustrate the application of the model.